Separation and identification of antioxidant peptides from foxtail millet (Setaria italica) prolamins enzymatic hydrolysate. Issue 6 (11th September 2019) - Ji, Zhongwei; Feng, Ruixue; Mao, Jian
Abstract: Background and objectives: Prolamins are the primary component of millet protein, constituting over 50% ( w / w ) of the total protein. This study aimed to prepare and identify bioactive peptides from millet prolamins (MP). Findings: Ultrasonic and heat treatment could change the secondary structure conformation of the protein and invert part of the α‐helices into β‐sheets or β‐turns. After these treatments, the degree of hydrolysis increased. The alcalase‐hydrolyzed fraction with molecular weight <1 kDa exhibited the highest antioxidant activity. The bioactive peptides were separated and purified by gel‐filtration chromatography and reversed‐phase high‐performance liquid chromatography. Two novel peptides with molecular weights of 522.3 and 785.5 Da were identified as Pro‐Phe‐Leu‐Phe (PFLF) and Ile‐Ala‐Leu‐Leu‐Ile‐Pro‐Phe (IALLIPF), respectively. Both peptides showed high antioxidant activity, especially PFLF, the 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging ability (RSA) of which was 149 μM TE/g protein, and the Oxygen radical absorbance capacity (ORAC) value reached 1, 180 μM TE/g protein. Conclusions: The results demonstrate that ultrasonic and heat treatment could enhance hydrolysis of MP by protease and antioxidant peptides with high DPPH RSA as well as ORAC value were purified and obtained. Significance and novelty: Ultrasonic and heat treatment increased degree of MP hydrolysis. Two antioxidant peptides were successfully obtained from millet prolamins.